2019
DOI: 10.1016/j.mcat.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and slurry phase ethylene polymerisation of rac-(PhBBI*)ZrCl2 immobilised on modified layered double hydroxides

Abstract: Rac-and meso-bis(1-hexamethylindenyl)phenylborane zirconium dichloride, {rac-, meso-(Ph BBI*)ZrCl2} has been synthesised and fully characterised. The slurry phase ethylene polymerisation performance of rac-(Ph BBI*)ZrCl2 immobilised on a range of methylaluminoxane (MAO)-modified, solvent-dispersed, high surface area layered double hydroxides (AMO/AIM-MgxAl-CO3 LDHs) have been studied. The polymerisation activities show a strong dependence on the nature of the LDH. Rac-(Ph BBI*)ZrCl2 supported on a MAOmodified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…28 The permethylindenyl ligand has previously been shown to enhance the activity of Cp*-based ligands both in metallocene and CGC analogues. 25,35–42 This is attributed to facile η 5 ,η 3 -haptotropic ring slip – which lowers the barrier to associative addition; 43–46 the steric kinetic stabilisation of the ligand; 47 and the positive inductive effect of polyalkylation resulting from σ–π hyperconjugation. 48 We have previously introduced the PHENI* ligand which is a development of PHENICS ligands, incorporating the many benefits of I*, and which shows higher activities both than the I* CGC analogues introduced by Williams et al and the indenyl PHENICS analogue.…”
Section: Resultsmentioning
confidence: 99%
“…28 The permethylindenyl ligand has previously been shown to enhance the activity of Cp*-based ligands both in metallocene and CGC analogues. 25,35–42 This is attributed to facile η 5 ,η 3 -haptotropic ring slip – which lowers the barrier to associative addition; 43–46 the steric kinetic stabilisation of the ligand; 47 and the positive inductive effect of polyalkylation resulting from σ–π hyperconjugation. 48 We have previously introduced the PHENI* ligand which is a development of PHENICS ligands, incorporating the many benefits of I*, and which shows higher activities both than the I* CGC analogues introduced by Williams et al and the indenyl PHENICS analogue.…”
Section: Resultsmentioning
confidence: 99%
“…A similar observation has been reported for ethylene homo-polymerization, wherein CO 2− 3 /A shows a marginally higher activity than the CO 2− 3 anion intercalated in MgAl LDH. [35] Notably, the Zr catalyst supported on NiFe with intercalated DDS − and NO − 3 anions showed relatively higher activities of 1020 and 893 kgEP mol −1 h −1 bar −1 , respectively, than their homogeneous analogs. Buffet et al [30] reported similar observations in the case of ethylene polymerization, wherein the intercalated sulfate anion in MgAl showed higher activity than the carbonate anion.…”
Section: Resultsmentioning
confidence: 97%
“…Other studies reported the application of LDH-supported metallocene catalysts for ethylene polymerization. [12,36,35] Kenyon et al reported the LDH-supported catalysts, thereby paying more attention to catalyst immobilization and tuning polyethylene properties. [36] In another study by Kenyon et al, the effect of LDH composition on the catalytic performance of metallocene was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LDHs have been used as nanofillers [ 24 , 25 ] and as catalyst support [ 20 , 26 , 27 , 28 , 29 ] in the polymer nanocomposites (polyethylene-PE, Polypropylene-PP) by in-situ polymerization. LDHs influence the MWD, crystallinity, polymer morphology, catalytic activities and improve flame retardancy.…”
Section: Introductionmentioning
confidence: 99%